The study of Islamic teachings in education: With an emphasis on behavioural gentleness - Pallathadka, Harikumar (HTS teologiese studies, 2023)
The human being is the most wonderful creation of God and the highest sign of his infinite power. Humanity is capable of achieving all divine perfections. God created them to reach the position of God’s closeness and God’s successor on Earth, and this path will not be realised except by the correct education. A human is a divine being who has settled in this earthly world, and correct education is the only way to achieve that sacred truth. Divine prophets have come to prepare the Earth for this great transformation in human existence and guide them to the light of divine teachings. There is no doubt that if human beings are not educated according to divine standards, they will remain at the level of animality. The Holy Qur’an, as the most precious Islamic divine book, presents the best way of education based on the knowledge of the truth of humanity and their needs. In addition, it is appropriate to discuss the role of behavioural gentleness in the education of people, and in this regard, the Qur’anic verses have been reviewed carefully. Therefore, the aim of this manuscript is to study the Islamic teachings in education with an emphasis on behavioural gentleness.Contribution: If curriculum planners and educators in general pay attention to Qur’anic teachings in education and base their curriculum and educational programs on Qur’anic teachings and according to characteristics and abilities and appropriateness of methods, and if the contents are paid attention to and educational programs are produced based on the will and authority of the educators, we will definitely witness progress and development in educational systems on the one hand and development and progress in all levels of life.